Biocompatible ferrite nanoparticles for hyperthermia: effect of polydispersity, anisotropy energy and inter-particle interaction. (27th February 2017) - Wadehra, Neha; Gupta, Ruby; Prakash, Bhanu; Sharma, Deepika; Chakraverty, S
Abstract: We have simulated the rise in temperature (Δ T ) of uniaxial single domain nanomagnets (particle size r) placed under alternating (AC) magnetic field (frequency ω ) in ' r - ω ' plane. Based on this, a phase space of 'Δ T max - r - ω ' has been constructed. This phase space suggests two bio-compatible ferrites namely Fe3 O4 and MnFe2 O4 which may generate necessary temperature for hyperthermia effect. Our simulated results further show that introduction of particle size distribution drastically reduces the efficiency of heat generation. On the other hand, introduction of inter-particle magnetic dipolar interactions may enhance the temperature rise.